1997
DOI: 10.1111/j.1440-1584.1997.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Community Competence and Empowerment: Strategies for Rural Change in Women's Health Service Planning and Delivery

Abstract: Rural women face a variety of health-related problems, some of which they share with their city sisters. However, the multiple responsibilities of women on the land, and their geographical isolation and lack of support, can lead to physical decline and increased mental strain. It is these factors which are often overlooked in the planning and allocation of funding and services to rural areas. This paper examines the application of community competence and empowerment measures in developing and implementing hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…There is a potential role here for ICTs, especially the Internet, but its configuration to date has not been informed by the needs of at least this group of users (nor, we would argue, those of many other groups). First, beyond simply ensuring connectedness in a technological sense, effective integration of ICTs in a broader system of health information provision to people in rural and remote areas must account for context and be framed, as Coakes and Kelly (1997) have suggested, in a model that accounts for community competence specific to rural areas. Second, the evolution of the socalled "Web 2.0," with its particular emphasis on online communities, connection, and collaboration, might be a way to integrate information with care.…”
Section: Resultsmentioning
confidence: 99%
“…There is a potential role here for ICTs, especially the Internet, but its configuration to date has not been informed by the needs of at least this group of users (nor, we would argue, those of many other groups). First, beyond simply ensuring connectedness in a technological sense, effective integration of ICTs in a broader system of health information provision to people in rural and remote areas must account for context and be framed, as Coakes and Kelly (1997) have suggested, in a model that accounts for community competence specific to rural areas. Second, the evolution of the socalled "Web 2.0," with its particular emphasis on online communities, connection, and collaboration, might be a way to integrate information with care.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that rural Australians have poor health indicators compared with the population residing in metropolitan areas 1 and have health needs that are different from urban dwellers 2 . It has also been shown that social accessibility or acceptability are more important considerations than geographical proximity when rural residents decide to consult a particular practitioner 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Rural Australia has a distinctive set of variables relating to geography, culture and social relationships that inhibit women’s ability to access and utilise quality health 2 . Most importantly, rural Australians are isolated geographically due to dispersed population patterns, and are therefore often required to travel long distances to access services, especially services of a specialist nature 3 .…”
Section: Introductionmentioning
confidence: 99%